Groundwater Guardians:: Linking Research, Policy, and People to Save Springs - Aisah, Intan Nur; Hardiansyah, Dito (SEAMEO BIOTROP, 2025)
Kulon Progo Regency in Indonesia is home to a rich variety of geological features, an underground landscape that holds great promise for water resources like natural springs. Yet, in 2019, the community of Girimulyo Subdistrict faced a troubling clean water shortage, highlighting a growing need for smarter water management. To better understand where water is available and how it flows, researchers turned to modern mapping tools. Using Geographic Information System (GIS) technology, along with field surveys and measurements of spring water flow, scientists set out to chart the location and behavior of springs across the region. They used ArcGIS software and a method called Nearest Neighbor Analysis to uncover patterns in the data. What they found was surprising: springs in Kulon Progo do not follow a regular pattern; they appear scattered randomly across the landscape. The strength of each spring’s water flow also varied, depending on the land’s slope and the type of soil. These findings are not just academic. They offer a practical foundation for improving how the region manages its water; a critical step toward preventing future water crises and ensuring clean water access for all. Want to know more? Let’s read this!